2021
DOI: 10.1590/1980-57642021dn15-020012
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of risk factors for dementia in middle- and older- aged people registered in Primary Health Care

Abstract: ABSTRACT. It is important to assess the prevalence of risk factors for dementia to slow down the progression and evolution of the disease, and to support interventions and prevention programs. Objective: We aimed to evaluate the prevalence of these factors in individuals registered in Primary Health Care in Brazil and their relationship with sex and age group. Methods: This was a cross-sectional and quantitative study with n=300 individuals. We evaluated the prevalence of main risk factors (low education, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 46 publications
0
2
0
1
Order By: Relevance
“…A análise de regressão confirmou diferença significativa para escolaridade e faixa etária, sendo que os mais velhos apresentaram maior prevalência de baixa escolaridade. 11 Uma metanálise no Reino Unido teve como objetivo detectar variáveis no registro de atenção primária que podem indicar risco de desenvolvimento de demência e assim ser combinadas em um modelo preditivo para ajudar a encontrar pacientes que não possuem um diagnóstico. Para isso foram selecionados 3836 artigos, dos quais 20 estudos eram elegíveis para inclusão, todos europeus, compreendendo > 1 milhão de pacientes.…”
Section: Resultsunclassified
“…A análise de regressão confirmou diferença significativa para escolaridade e faixa etária, sendo que os mais velhos apresentaram maior prevalência de baixa escolaridade. 11 Uma metanálise no Reino Unido teve como objetivo detectar variáveis no registro de atenção primária que podem indicar risco de desenvolvimento de demência e assim ser combinadas em um modelo preditivo para ajudar a encontrar pacientes que não possuem um diagnóstico. Para isso foram selecionados 3836 artigos, dos quais 20 estudos eram elegíveis para inclusão, todos europeus, compreendendo > 1 milhão de pacientes.…”
Section: Resultsunclassified
“…High cholesterol levels are associated with an elevated risk of memory loss and AD. This implies that the risk of developing neurodegenerative diseases such as dementia and AD is dramatically increased in older adults [22].…”
Section: Dysregulation Of Lipid Homeostasis and Alzheimer Diseasementioning
confidence: 99%
“…Age is a crucial factor in the prevalence of dementia, as it is strongly associated with the risk of developing dementia. Recent studies have indicated a decline in the age-adjusted incidence of dementia in the United States and other developed countries over the past two decades, which is believed to be linked to a higher level of formal education [ 5 ]. Age-adjusted dementia refers to the adjustment of the statistical prevalence of dementia to account for variations in age distribution of the population.…”
Section: Introductionmentioning
confidence: 99%